2005
DOI: 10.1136/bmj.38476.471088.3a
|View full text |Cite
|
Sign up to set email alerts
|

Systematic comparison of four sources of drug information regarding adjustment of dose for renal function

Abstract: Objective To compare advice on dosage adjustment for renal impairment provided by four commonly used secondary pharmacotherapeutic sources. Design Systematic comparison of the definitions of renal impairment, recommendations for dosage adjustment, and the evidence in support of these recommendations in four information sources. Data sources British National Formulary, Martindale: the Complete Drug Reference, American Hospital Formulary System Drug Information, and Drug Prescribing in Renal Failure.Review metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 2 publications
1
62
0
5
Order By: Relevance
“…Moreover, there is a confirmed lack of consistency in the different consulted sources. This situation is also found in the general dosage recommendations as well as in the available kinetic data of drugs, mainly in the E H , as it happens in the adjustment for renal insufficiency (25).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, there is a confirmed lack of consistency in the different consulted sources. This situation is also found in the general dosage recommendations as well as in the available kinetic data of drugs, mainly in the E H , as it happens in the adjustment for renal insufficiency (25).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, Vidal et al and Khanal et al had described six categories of dose adjustment methods [9,16] and we modified their categories. Using this modified classification, we compared the consistency of information and its presentation in each of the five sources.…”
Section: Methodsmentioning
confidence: 99%
“…However, a previous systematic assessment of drug dosage recommendations for various degrees of renal function revealed that tertiary drug information references may not be suitable for clinical use because of wide variation in the recommendations. 10 The authors of a recent editorial revealed that less than 20% of currently used drugs have been studied in the setting of CRRT.…”
Section: Introductionmentioning
confidence: 99%